Grain Yield, Rice Seedlings and Transplanting Quantity in Response to Decreased Sowing Rate under Precision Drill Sowing - Liqiang Dong; Tiexin Yang; Rui Li; Liang Ma; Yingying Feng; Yuedong Li (Agriculture)
Mechanical transplanting has become an important part of modern Chinese rice production, and an inadequate sowing rate severely inhibits rice seedling growth and development. Precision drill sowing is an effective method for obtaining higher quality seedlings during machine transplanting. There is a lack of systematic research on the precision drilling of rice. Therefore, we carried out research on the quality of machine-transplanted seedlings and precision drill sowing transplantation. A greenhouse experiment (Liaoning Rice Research Institute) and field experiment (Sujiatun District, Shenyang City, Liaoning Province, China) were conducted between 2020 and 2021 to analyze the influence of precision drill sowing on rice growth and yield. Precision drill sowing was conducted at four sowing rates (3400, 3600, 3800, and 4000 seeds/tray), and traditional broadcasting was also conducted at a sowing rate of 4000 seeds/tray. We evaluated the seedling rice quality, physiological and biochemical characteristics and transplanting quantity. The results indicated that precision drill sowing at a sowing rate of 3400 seeds/tray resulted in the highest plumpness value (0.18) and seedling strength index (0.42) of individual plants. However, the empty hill rate was as high as 3.05%, which did not satisfy the field seedling number requirement. Precision drill sowing at a sowing rate of 4000 seeds/tray resulted in the lowest physiological (the average levels of SOD, POD and soluble protein were 311.78 µg/g, 8.25 µg/g and 1.28 µg/g) and biochemical indices of individual plants. The damaged seedling rate increased by 2.07%, and the dead seedling rate increased by 0.25%, resulting in poor seedling and transplanting quality. In this study, 3800 seeds/tray was the best option and had the highest yields of 10,776.60 kg/ha and 10,730.85 kg/ha over the two years. This sowing approach performs well in terms of field transplanting, provides a balance point between seedling number and quality and is conducive to rice yield production. The results of this study are important for improving rice seedling quality, enhancing field transplanting quantity and increasing rice yield and food security.